2016
DOI: 10.1038/srep29508
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of temporal evolution of quantum dot surface chemistry by surface-enhanced Raman scattering

Abstract: Temporal evolution of surface chemistry during oxidation of silicon quantum dot (Si-QD) surfaces were probed using surface-enhanced Raman scattering (SERS). A monolayer of hydrogen and chlorine terminated plasma-synthesized Si-QDs were spin-coated on silver oxide thin films. A clearly enhanced signal of surface modes, including Si-Clx and Si-Hx modes were observed from as-synthesized Si-QDs as a result of the plasmonic enhancement of the Raman signal at Si-QD/silver oxide interface. Upon oxidation, a gradual d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…For example, some organophosphorus compounds, such as methylparathiol and dimethoate, that exist in pesticides were identified at the nanogram level 8 . Because water molecules scatter weakly in Raman experiments, it has made the SERS approach an attractive choice to conduct useful characterization of samples 9 10 11 .…”
mentioning
confidence: 99%
“…For example, some organophosphorus compounds, such as methylparathiol and dimethoate, that exist in pesticides were identified at the nanogram level 8 . Because water molecules scatter weakly in Raman experiments, it has made the SERS approach an attractive choice to conduct useful characterization of samples 9 10 11 .…”
mentioning
confidence: 99%
“…For the surface chemistry analysis, Fourier transform infrared spectroscopy (FTIR) is commonly used. In a series of recent publications, we have demonstrated that Raman spectroscopy can be used as a standard diagnostic tool for the analysis of the size distribution and surface chemistry of Si‐NPs. Especially on size distribution analysis, we have shown that, Raman spectroscopy is non‐destructive and time‐efficient, and gives reliable results as the analyses agree well with other size analysis techniques like TEM and PL.…”
Section: Resultsmentioning
confidence: 99%
“…One of the mostly observed functionalization process of Si‐NPs in plasmas occurs via the coverage of nanoparticle surfaces by the dissociated atoms of the Si‐containing precursor during the synthesis. It was reported that using precursors of SiH 4 , and SiCl 4 leads to the formation of Si‐NPs covered with hydrogen and chlorine, respectively. The research demonstrated that hydrogen terminated Si‐NPs are significantly more robust against oxidation in air than chlorine terminated Si‐NP surfaces, which oxidizes almost instantly …”
Section: Synthesis and Functionalization Of Si‐nps In Plasmasmentioning
confidence: 99%
“…Hot spots are also essential to future applications of plasmonics in photochemistry or photovoltaics [20]. A few papers have applied SERS to QDs of different materials : CdS [27], CdSe [28][29][30], PbS [31], SnO2 [32] or Si [33]. SERS is a promising technique for QD detection and may be applied for the detection of traces of nanoparticles, for the detection of biomarkers or for in-situ tracking of the nanoparticles'surface chemical properties such as their oxidation [31,33].…”
Section: Introductionmentioning
confidence: 99%